High-temperature electromagnons in the magnetically induced multiferroic cupric oxide driven by intersublattice exchange - Jones, S; Gaw, S; Doig, K; Prabhakaran, D; Hétroy Wheeler, E; Boothroyd, A; Lloyd-Hughes, J (Springer Nature, 2014)
Magnetically induced ferroelectric multiferroics present an exciting new paradigm in the design of multifunctional materials, by intimately coupling magnetic and polar order. Magnetoelectricity creates a novel quasiparticle excitation--the electromagnon--at terahertz frequencies, with spectral signatures that unveil important spin interactions. To date, electromagnons have been discovered at low temperature (<70 K) and predominantly in rare-earth compounds such as RMnO3. Here we demonstrate using terahertz time-domain spectroscopy that intersublattice exchange in the improper multiferroic cupric oxide (CuO) creates electromagnons at substantially elevated temperatures (213-230 K). Dynamic magnetoelectric coupling can therefore be achieved in materials, such as CuO, that exhibit minimal static cross-coupling. The electromagnon strength and energy track the static polarization, highlighting the importance of the underlying cycloidal spin structure. Polarized neutron scattering and terahertz spectroscopy identify a magnon in the antiferromagnetic ground state, with a temperature dependence that suggests a significant role for biquadratic exchange.